como faço a equação de 6x - 7 (1 - x) - (10x + 4) = 0
Soluções para a tarefa
Respondido por
3
6x-7(1-x)-(10x+4)=0
6x-7+7x-(10x+4)=0
6x-7+7x-10x-4=0
6x+7x-10x=7+4
13x-10x=11
3x=11
x=11/3
6x-7+7x-(10x+4)=0
6x-7+7x-10x-4=0
6x+7x-10x=7+4
13x-10x=11
3x=11
x=11/3
isabellasalvat:
esta errado é +7x
Respondido por
0
6x -7+7x-10x+4=0
3x-3=0
3x=3
x=3/3
×=1
Espero ter ajudado!
3x-3=0
3x=3
x=3/3
×=1
Espero ter ajudado!
Perguntas interessantes
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
Física,
1 ano atrás
Ed. Técnica,
1 ano atrás